Vulnerabilities of developing countries to food commodity price risks: International responses - Alexandros Sarris (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
The recent period of high and volatile world food commodity prices has spurred many discussions initiatives and proposals for market regulation and enhancements. This has been of particular concern to the Net Food Importing Developing Countries (NFIDCs), especially the Least Developed Countries (LDCs) among them. The paper suggests that the main concerns of these countries involve market unpredictability, uncertainty about contract enforcement in periods of crisis, and financial constraints in importing food staples. A review of the appropriate policies to deal with risks of NFIDCS reveals that there are several policies that have been proposed, which if implemented at international level could alleviate the concerns of NFIDCs. However, a review of actions and initiatives taken at the highest international levels reveals that while the rhetoric has been there, the actual actions and financing for them have been short of the objectives. On the other hand considerable legislative activity in the US and the EU has aimed at curbing excess speculation in derivatives markets under the assumption that these markets are the main cause of market upheavals, something, however, that has not been scientifically confirmed. It thus seems that there is still a lot to be done to insure NFIDCs against market food commodity market shocks and volatility.
Keywords: 330